Laboratory experiments in innovation research: A methodological overview and a review of the current literature - Julia Brüggemann; Kilian Bizer (Journal of Innovation and Entrepreneurship, 2016)
Innovation research has developed a broad set of methodological approaches in recent decades. In this paper, we propose laboratory experiments as a fruitful methodological addition to the existing methods in innovation research. Therefore, we provide an overview of the existing methods, discuss the advantages and limitations of laboratory experiments, and review experimental studies dealing with different fields of innovation policy, namely intellectual property rights, financial instruments, payment schemes, and R&D competition. These studies show that laboratory experiments can fruitfully complement the established methods in innovation research and provide novel empirical evidence by creating and analyzing counterfactual situations.
Keywords: C90; L50; O38; 650; Innovation research; Laboratory experiments; Methodology